HDI XMAS July 15, 2019. Dorothy Reid photos. - Barrett, Terra (2000)
A photo of (front row) Dalas Pitcher, Calvin Legge, Dorothy Reid, Christine Sooley, Howard Sooley, Mary Vivian, Boyd Vivian, (back row) Percy Chislett, Stan Reid, Robert Hiscock, and Donna Hiscock at a Christmas party in 2000.